Validity of the Innovative KIT and Biology Practicum Guide Based on Local Potential - Agustina Ambar Pertiwi; Irma Rahmawati; Wafiq Azizah; Isnaniah (Bioeduca : Journal of Biology Education, 2026)
Learning activities that facilitate the essence of natural science are practical activities. Practical activities can improve science process skills, psychomotor skills, and mastery of material concepts. Facilities and infrastructure that support practical activities are important for every school to have. However, not all schools can provide laboratories and practical tools, especially schools in rural areas. This study aims to describe the validity of the innovative biology practical kit (KIT) and guides developed based on local potential. This type of research is Research and Development (RnD) with an ADDIE research design (analyze, design, develop, implement, and evaluate). Data were collected using a questionnaire technique and analyzed descriptively quantitatively. Based on the results of the validity test, the innovative biology practical kit (KIT) and the biology practical guide based on local potential that were developed are included in the criteria of very valid with an average percentage of 88.89% for the innovative biology practical kit and 86.97% for the biology practical guide. This indicates that the innovative biology practical kit based on local potential and the biology practical guide can be used in learning.